Men in breast cancer families: a preliminary qualitative study of awareness and experience. Issue 9 (September 1998) - McAllister, M F; Evans, D G; Ormiston, W; Daly, P
Abstract : In inherited forms of breast cancer, attention in clinical genetics services has focused on women because they are most at risk of developing cancer. Men at risk of transmitting a predisposing gene mutation are less likely to have a genetic test than the women in these families. This preliminary study investigates the perspective of the brothers of women with familial breast cancer and is based on qualitative analysis of 22 semistructured interviews using an attenuated form of Grounded Theory. There is an awareness among these men (without having had genetic counselling) that the breast cancer in their families is inherited. Some of them harbour fear of developing cancer themselves and many are concerned that their daughters might develop breast cancer. Some appeared to use avoidance as a coping strategy. The men were very often excluded from family conversations about breast cancer. Implications for the provision of genetic counselling for these families are discussed.